Hubungan Infeksi Saluran Kemih pada Ibu Hamil dengan Kejadian Ketuban Pecah Dini di Rumah Sakit Umum Sylvani Binjai periode Januari 2020 – Desember 2021. - Priccilia, Agnes Bella; Hutasoit, Eka Samuel P; Rimbun, Surjadi (Universitas Methodist Indonesia, 2022)
Background: In Indonesia, the incidence of urinary tract infections can reach 90-100 cases per 100,000 population based on data from the Ministry of Health. Urinary tract infection is a disease that often occurs in pregnant women, which is caused by anatomical and physiological changes during pregnancy. Urinary tract infections that occur during pregnancy can cause complications that can affect the mother and fetus, one of which is the incidence of premature rupture of membranes, which is a state of rupture of the amniotic membrane before the delivery process. Objective: This study aims to determine the relationship between urinary tract infections in pregnant women and the incidence of premature rupture of membranes. Method This study uses a cross sectional method which was conducted in May, the samples taken were 45 samples. Data was obtained through secondary patient data contained in the medical record room at Sylvani Binjai General Hospital for the period January 2020 - December 2021. Result : Based on the results of the chi square statistical test that has been carried out, it is found that p value = 0.042 (p = <0.05) Conclusion: There is a relationship between urinary tract infections and the incidence of premature rupture of membranes at the Sylvani Binjai General Hospital for the period January 2020 - December 2021.